A geometric formulation of supersymmetry. Issue 1 (5th December 2016) - Freedman, Daniel Z.; Roest, Diederik; Van Proeyen, Antoine
Abstract : The scalar fields of supersymmetric models are coordinates of a geometric space. Here a formulation of supersymmetry that is covariant with respect to reparametrizations of this target space is proposed by introduction of modified supersymmetry variations and redefined auxiliary fields transforming covariantly under reparametrizations. The resulting action and transformation laws are manifestly covariant and highlight the geometric structure of the supersymmetric theory. The covariant methods are developed first for general theories (not necessarily supersymmetric) whose scalar fields are coordinates of a Riemannian target space. Abstract : The scalar fields of supersymmetric models are coordinates of a geometric space. We propose a formulation of supersymmetry that is covariant with respect to reparametrizations of this target space. Employing chiral multiplets as an example, we introduce modified supersymmetry variations and redefined auxiliary fields that transform covariantly under reparametrizations. The resulting action and transformation laws are manifestly covariant and highlight the geometric structure of the supersymmetric theory. The covariant methods are developed first for general theories (not necessarily supersymmetric) whose scalar fields are coordinates of a Riemannian target space.